Genetic analysis of attenuation markers of cold-adapted X-31 influenza live vaccine donor strain. Issue 11 (8th March 2016) - Jang, Yo Han; Jung, Eun-Ju; Lee, Kwang-Hee; Byun, Young Ho; Yang, Seung Won; Seong, Baik Lin
Highlights: Cold-adaptation of X-31 virus resulted in sequence changes in the internal genes. Seven of 17 amino acid substitutions were highly unique to cold-adaptation. Contribution of each gene to attenuation was analyzed under PR8 virus background. NP gene was the most pronounced genetic marker for the ca, ts, and att phenotypes. A balanced contribution of each internal gene supports genetic stability of X-31 ca. Abstract: Cold-adapted live attenuated influenza vaccines (CAIVs) have been considered as a safe prophylactic measure to prevent influenza virus infections. The safety of a CAIV depends largely on genetic markers that confer specific attenuation phenotypes. Previous studies with other CAIVs reported that polymerase genes were primarily responsible for the attenuation. Here, we analyzed the genetic mutations and their phenotypic contribution in the X-31 ca strain, a recently developed alternative CAIV donor strain. During the cold-adaptation of its parental X-31 virus, various numbers of sequence changes were accumulated in all six internal genes. Phenotypic analysis with single-gene and multiple-gene reassortant viruses suggests that NP gene makes the largest contribution to the cold-adapted (ca) and temperature-sensitive (ts) characters, while the remaining other internal genes also impart attenuation characters with varying degrees. A balanced contribution of all internal genes to the attenuation suggests that X-31 ca could serve as an ideal master donor strain for CAIVs preventing influenza epidemics and pandemics.